Indonesian Tourist’ Perceived Sacredness on Pilgrimage Journey - Rohman, Fatchur (APMBA (Asia Pacific Management and Business Application), 2020)
This study explores and identifies the precise measurement of perceived sacredness of Indonesian tourist’s perceived sacredness on their pilgrimage journey. Indonesia is a unique country which is having more than five major religions adopted by its population, thus we suggested they have a different perception of sacredness on spiritual destination. The methodology used in this study are using culture-based construct design to identify the items and indicators that could measure the Indonesian tourist’s perceived sacredness. Thirteen items were identified, but only eight items were accepted as a valid and reliable measurement of the Indonesian tourist’s perceived sacredness. Three indicators could be built from the items, they are (1) Spiritual Attractiveness, (2) Historic Spiritual Value, and (3) Spiritual Activities. The finding(s) on this research could be used for future research, especially to examining the relationship between perceived sacredness toward the Indonesian tourist’s behavior.